The Effect of Good Corporate Governance and Company Size on Banking Financial Performance with Dividend Policy as a Moderating Variable (Study on Banking Companies that Go Public on the Indonesia Stock Exchange for the 2018-2023 Period) - Moeslem, Aqsal Wildan; Khatik, Nur; Hardiwinoto, Hardiwinoto (Economics and Business International Conference Proceeding, 2024)
This study aims to empirically prove the influence of Good Corporate Governance and company size on financial performance with dividend policy as a moderating variable. The method used in this study is a quantitative approach. The data used is secondary data of banking companies listed on the Indonesia Stock Exchange during 2018-2023. Sampling using the purposive sampling technique, 180 companies were selected as samples. The analysis technique carried out in this study is a panel data regression model using Eviews 12 software. The results of this research show that the board of directors and institutional ownership have a positive and significant effect on financial performance. Company size has a negative and significant effect on financial performance. Meanwhile, the independent board of commissioners and audit committee have no influence. In the regression analysis, dividend policy moderation was not able to moderate the influence of the independent board of commissioners, board of directors, audit committee and company size. Meanwhile, dividend policy is able to weaken the influence of institutional ownership on financial performance.